Cultural Variation in Reactions to a Group Member’s Vicarious Choice and the Role of Rejection Avoidance - Eisen, Charis; Ishii, Keiko (Frontiers in Psychology, 2019)
Extending the literature on culture and the personal or interpersonal construction of choices, this research investigates consequences of an ingroup member’s vicarious decision for the entire group and the mechanism behind cultural variation. In Study 1, Japanese people showed, compared to Germans, greater acceptance of vicarious choice and evaluated the ingroup member who had chosen on their behalf more positively. Using mediation analyses and priming methods, Studies 2 and 3 identified rejection avoidance to partly explain culturally diverse reactions to vicarious choices. These findings suggest that the mechanism behind cultural differences in choice is related to variation in strength of the motivation to maintain social approval.